The Role of Mechanical Engineering in the Development of Environmentally Friendly Electric Vehicles - Zhang Wei; Snyder Bradford; Xie Guilin (Journal of Moeslim Research Technik, 2024)
In an effort to address environmental issues caused by greenhouse gas emissions and air pollution from fossil fuel vehicles, the development of electric vehicles is a promising solution. Electric vehicles offer a more environmentally friendly alternative and have the potential to reduce dependence on fossil fuels. The role of mechanical engineering in the innovation and development of electric vehicle technology is crucial to achieve higher efficiency and minimal environmental impact. This research aims to analyze the contribution of mechanical engineering in the development of environmentally friendly electric vehicles, including the identification of technologies and methods used to improve the performance and efficiency of electric vehicles. This research uses a qualitative method with a literature study approach and comparative analysis. Data were collected from various scientific and technical sources, including relevant journals, books, and industry publications. Technical innovations in the design of electric motors, energy storage systems, and materials used in electric vehicles were analyzed. The results show that mechanical engineering has an important role in various aspects of electric vehicle development. Innovations in electric motor design such as the use of permanent magnet synchronous motors (PMSM) and induction motors have improved efficiency and performance. The development of batteries with high energy density and good thermal management is also key in improving the range and reliability of electric vehicles. In addition, the use of lightweight and strong materials in vehicle construction contributes to reducing energy consumption. Mechanical engineering plays a crucial role in the development of more efficient and environmentally friendly electric vehicles. Through various technical innovations, electric vehicles can be a sustainable solution for future transportation, with great potential to reduce negative impacts on the environment. The implementation of new technologies in motor design, energy storage systems, and vehicle materials are decisive factors i